Docking Unit Joining Omni Wheel Robot and Mobile Robot - Naoki Igo; Daichi Fujita; Ryoma Hanabusa; Yasuto Nagase; Satoshi Mitsui; Toshifumi Satake (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2019)
This research realizes a docking unit joining omni wheel robot and mobile robot. The omni wheel robot cannot move on rough ground. In order to move on rough ground, a mobile robot that can move with the omni wheel robot is required. The docking unit aims at a unit that can be used without remodeling omni wheel robot. The docking unit realized by this research can store the fixed part of the omni wheel robot. When omni wheel robot is mounted, the mounting surface is flat because the fixed parts are stored, and the omni wheel robot can be mounted by sliding. As a result, we designed a mechanism to connect the fixed parts to store the parts that fix the omni wheel robot. And the fixed parts with the mechanism were made.